2018
DOI: 10.3389/fmicb.2018.00647
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acetone Fraction From Buchenavia tomentosa Aqueous Extract and Gallic Acid on Candida albicans Biofilms and Virulence Factors

Abstract: A promising anti-Candida activity of Buchenavia tomentosa extracts was recently described. In the present work, experiments were carried out to determine the fraction with higher antifungal activity from a B. tomentosa extract. Acetone fraction (AF) was obtained from the aqueous extract from dried leaves (5 min/100°C) and it was the most effective one. Gallic acid (GA) was identified by electrospray ionization mass spectrometry (ESI–MS) and also chosen to perform antifungal tests due to its promising activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 36 publications
2
16
0
Order By: Relevance
“…Previous works reported the predominant presence of flavonoids and alkaloids in B. tetraphylla and other species from the same genus [20,21,43,44]. In this present research, the most bioactive fractions (BTFC and BTFD) showed a similar chemical composition with the presence of aliphatic (terpenes, fatty acids, carbohydrates) and aromatic compounds (phenolic compounds).…”
Section: Discussionsupporting
confidence: 73%
“…Previous works reported the predominant presence of flavonoids and alkaloids in B. tetraphylla and other species from the same genus [20,21,43,44]. In this present research, the most bioactive fractions (BTFC and BTFD) showed a similar chemical composition with the presence of aliphatic (terpenes, fatty acids, carbohydrates) and aromatic compounds (phenolic compounds).…”
Section: Discussionsupporting
confidence: 73%
“…In this way, the extracts could be acting on extracellular matrix components, which are more present in mature biofilms. Similar results were obtained by Teodoro et al [22] when studying the effects of a Buchenavia tomentosa acetone fraction on Candida biofilms.…”
Section: Discussionsupporting
confidence: 88%
“…Alalwan et al [25] performed different experiments with curcumin and found that this substance interferes with the adhesion of C. albicans SC5314 to denture materials. Teodoro et al [22] demonstrated that an acetone fraction from a Buchenavia tomentosa extract had the ability to inhibit C. albicans ATCC 18804 and C. albicans SC 5314 adherence and to disrupt 48 h biofilm. However, they also verified that the acetone fraction and gallic acid showed slight to moderate toxicity to Vero cells.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings have shown an antibiofilm activity superior to that shown by other studies with natural products. 36,37 Although we used higher concentrations, we proved that they are well below the dose considered toxic in our model in vivo.…”
Section: Discussionmentioning
confidence: 76%